BIBLIOMETRIC ANALYSIS OF ECOTOURISM IN NATIONAL ARTICLES - SARI, Cemali; DELEN, Nehir Nur (SSD Journal, 2021)
Ecotourism is a type of tourism that is made by protecting the environment and being responsible for nature. In this study, it is aimed to examine the TR Indexed articles written between 2010-2021 on ecotourism. The method of the study is the literature review. Articles labeled ecotourism and types of ecotourism were scanned at the determined internet addresses. There were 296 articles identified and they were examined by bibliometric analysis within predetermined criteria.As a result of the analysis, it was determined that the most publications were made in 2019 among the years determined, and the most published journal type was the journals of the social sciences institutes of the universities. As a result of the analysis according to the institutions to which the authors are affiliated, Tourism Management is in the first place. The geography department is in the second place and follows tourism management. In terms of ecotourism types, the most publications were related to health tourism. While the most preferred method in data collection methods is interview, statistical analysis is the most preferred type in analysis type. The rate of articles that do not specify methods and analysis is quite high, with a rate of 26%.